2020
DOI: 10.3390/polym12040967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Subtropical Natural Exposure on the Bond Behavior of FRP-Concrete Interface

Abstract: Subtropical natural exposure may significantly affect the bonding behavior of fiber reinforced polymer (FRP) externally bonded to concrete. To study the effect of subtropical natural climates on the FRP-concrete interface, natural exposure tests and an analytical approach were carried out on specimens externally bonded with carbon fiber reinforced polymer (CFRP) and basalt fiber reinforced polymer (BFRP). The bilinear bond stress-slip relationships for different exposure periods were derived from the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The accuracy of the bond-slip relationship considered in the FE model has been demonstrated in many studies. Based on test results [35], the main bonding parameters of the epoxy adhesive were τ max = 5.301 MPa and S 0 = 0.0689 mm, which were in good agreement with the values calculated using Equations ( 1)-( 3). The debonding failure occurred when the greatest shear stress on the CFRP-concrete interface reached the interfacial bond strength τ max .…”
Section: Failure Criteriasupporting
confidence: 80%
See 1 more Smart Citation
“…The accuracy of the bond-slip relationship considered in the FE model has been demonstrated in many studies. Based on test results [35], the main bonding parameters of the epoxy adhesive were τ max = 5.301 MPa and S 0 = 0.0689 mm, which were in good agreement with the values calculated using Equations ( 1)-( 3). The debonding failure occurred when the greatest shear stress on the CFRP-concrete interface reached the interfacial bond strength τ max .…”
Section: Failure Criteriasupporting
confidence: 80%
“…For RC girders strengthened with prestressed CFRP, the main failure modes include CFRP fracture at the bottom of the midspan, concrete crushing at the top of the RC girders, yielding of the main reinforcement steel bars, and CFRP-concrete interfacial debonding failure [7]. Many studies [7,27,35] have shown that CFRP-concrete interfacial debonding failure and CFRP fracture frequently occur with increasing prestress levels. So far, most concrete specimens used for prestressed CFRP strengthening experiments have had rectangular or T-shaped cross-sections, and there have been few studies describing the failure modes of hollow box girders strengthened with prestressed CFRP.…”
Section: Failure Criteriamentioning
confidence: 99%
“…After 12 months of exposure, the interfacial bond behavior was stable. In precious work [40], the effect of natural subtropical exposure on CFRP-concrete interface was studied.…”
Section: Bond-slip Model Of Cfrp-concrete Interface After Exposurementioning
confidence: 99%